Transformation of hydrophysical properties of drained peat soils under the influence of anthropogenic factors - Скрипніченко C. В.; Скиба, Г. В. (Scientific Progress & Innovations, 2016)
The process of transformation in the dynamics of hydrophysical properties of drained peat soils under the influence of long-term intensive agricultural use is analyzed. Transformation of the structure parameters of the peat soil determines the orientation of the evolutionary process in the dynamics of hydrophysical constants. The most effective parameters of the peat soil structure and hydrophysical properties are formed when introducing single-cropping of perennial grass, herb-cultivated and corn-herb-cultivated crop rotation. The complexity of rational use of the drained peat soils is in transformation of their potential fertility into effective.